2007
DOI: 10.1152/ajpregu.00182.2007
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the febrile response induced by fibroblast-stimulating lipopeptide-1 in guinea pigs

Abstract: Recently, it has been shown that the Toll-like receptors-2 and -6 agonist fibroblast-stimulating lipopeptide-1 (FSL-1) have the capacity to induce fever and sickness behavior in rats. Since the mechanisms of the fever-inducing effects of FSL-1 are still unknown, we tested the pyrogenic properties of FSL-1 in guinea pigs and assessed a role for TNF-alpha and prostaglandins in the manifestation of the febrile response to this substance. Intra-arterial and intraperitoneal injections of FSL-1 caused dose-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 52 publications
2
13
0
Order By: Relevance
“…This relationship was confirmed by the use of TNF binding protein. TNFbp blocked the pyrogenic effect of FSL-1 and its ability to induce IL-6 expression (Greis et al, 2007). Zymosan, a yeast particulate, given to rats induced a fever and diminished a motivated behavior: decreased consumption of sweetened cereal (Cremeans-Smith and Newberry, 2003).…”
Section: Tlr2 Heterodimers and Tlr4: Membrane Lipidsmentioning
confidence: 99%
“…This relationship was confirmed by the use of TNF binding protein. TNFbp blocked the pyrogenic effect of FSL-1 and its ability to induce IL-6 expression (Greis et al, 2007). Zymosan, a yeast particulate, given to rats induced a fever and diminished a motivated behavior: decreased consumption of sweetened cereal (Cremeans-Smith and Newberry, 2003).…”
Section: Tlr2 Heterodimers and Tlr4: Membrane Lipidsmentioning
confidence: 99%
“…Importantly, several studies (including in our laboratory) showed that TLR2, TLR5, and TLR9 agonists up-regulated PGE 2 in vivo [14], [16], [17]. While TLR2 and TLR9 agonists signal exclusively through adaptor molecule MyD88, TLR4 signaling may proceed via either MyD88 or through TRIF resulting in activation of interferon regulatory factor (IRF)-3 and a subsequent induction of the type 1 interferon (IFN-β) [18].…”
Section: Introductionmentioning
confidence: 96%
“…In addition to LPS, other TLR agonists have been shown to induce fever in animal models: the TLR2 agonists, macrophage-activating lipopeptide-2 (MALP-2) from Mycoplasma fermentans ( M. fermentans ), and a synthetic analogue of fibroblast-stimulating lipopetide-1 (FSL-1) spanning the NH 2 -termial sequence of a lipoprotein from M. salivarium , as well as TLR9 agonists synthetic oligonucleotide (ODN) of bacterial DNA CpG [15][17]. Importantly, several studies (including in our laboratory) showed that TLR2, TLR5, and TLR9 agonists up-regulated PGE 2 in vivo [14], [16], [17].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, other investigators noted that circulating IL-6 levels remained unaffected after intra-arterial or peritoneal injection of diclofenac [26]. Moreover, investigating the modulatory effects of diclofenac on IL-6 and prostaglandin (PG) levels showed that diclofenac significantly decreased PGE2 production but had no significant effect on IL-6 levels [27].…”
Section: Discussionmentioning
confidence: 96%